Learn correct English conservation through pictures - Singh, S. P.; Gupta, Prashant (New Delhi : Dreamland Publications.)
Contents v. 1-2 : Book on conversation covering every topic from day -to-day life. -- v. 3. Office English -- v.4. Business English. v. 5. Conversation through popular English phrases.
Keywords: English language -- Conversation phrase books